Use of Routine Complete Blood Count Results to Rule Out Anaplasmosis Without the Need for Specific Diagnostic Testing. (2nd May 2019) - Turbett, Sarah E; Anahtar, Melis N; Pattanayak, Vikram; Azar, Marwan M; Coffey, K C; Eng, George; Rudolf, Joseph W; Lewandrowski, Kent B; Baron, Jason; Rosenberg, Eric S; Branda, John A
Abstract: Background: Anaplasmosis presents with fever, headache, and laboratory abnormalities including leukopenia and thrombocytopenia. Polymerase chain reaction (PCR) is the preferred diagnostic but is overutilized. We determined if routine laboratory tests could exclude anaplasmosis, improving PCR utilization. Methods: Anaplasma PCR results from a 3-year period, with associated complete blood count (CBC) and liver function test results, were retrospectively reviewed. PCR rejection criteria, based on white blood cell (WBC) and platelet (PLT) counts, were developed and prospectively applied in a mock stewardship program. If rejection criteria were met, a committee mock-refused PCR unless the patient was clinically unstable or immunocompromised. Results: WBC and PLT counts were the most actionable routine tests for excluding anaplasmosis. Retrospective review demonstrated that rejection criteria of WBC ≥11 000 cells/µL or PLT ≥300 000 cells/µL would have led to PCR refusal in 428 of 1685 true-negative cases (25%) and 3 of 66 true-positive cases (5%) involving clinically unstable or immunocompromised patients. In the prospective phase, 155 of 663 PCR requests (23%) met rejection criteria and were reviewed by committee, which endorsed refusal in 110 of 155 cases (71%) and approval in 45 (29%), based on clinical criteria. PCR was negative in all 45 committee-approved cases. Only 1 of 110 mock-refused requests yielded a positive PCR result; this patient was already receiving doxycycline at the time of testing. Conclusions: A CBC-based stewardship algorithm would reduce unnecessary Anaplasma PCR testing, without missing active cases. Although the prospectively evaluated screening approach involved medical record review, this was unnecessary to prevent errors and could be replaced by a rejection comment specifying clinical situations that might warrant overriding the algorithm. Abstract : A laboratory screening algorithm using total white blood cell and platelet count cutoff values can be used to rule out anaplasmosis and reduce overutilization of Anaplasma polymerase chain reaction testing, even when disease incidence is relatively high.